MANAJEMEN PENDIDIKAN ISLAM SEBAGAI DISIPLIN ILMU - Nur Sahfitri; Ida Wahyuni Lubis, Amat Da’im, Wiyono, Imam Subekti (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The study of Islamic Education Management focuses on certain formal and material elements. To improve the efficiency of managing Islamic educational institutions, this study attempts to combine Islamic principles with contemporary management techniques. Islamic education must balance between maintaining uniqueness and remaining relevant in the face of globalization. The purpose of this study is to examine the nature, extent, characteristics, and evolution of Islamic education management as a field of study. This study uses a descriptive-analytical methodology combined with a qualitative approach. To understand the ideas, practices, and applications of Islamic education management in the context of globalization, data collection methods include documentation and literature review. The information is reviewed both phenomenologically to examine how these ideas are applied in the contemporary world and hermeneutically to understand how Islamic revelation and culture are integrated. The results show that Islamic education management has become a recognized academic field and can adapt to contemporary technology while maintaining the core principles of Islam.